2017
DOI: 10.3847/1538-4357/aa5d12
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Interstellar Gas Properties with Hi Spectral Lines: A Comparison between Synthetic Spectra and 21-SPONGE

Abstract: We analyze synthetic neutral hydrogen (H I) absorption and emission spectral lines from a high-resolution, threedimensional hydrodynamical simulation to quantify how well observational methods recover the physical properties of interstellar gas. We present a new method for uniformly decomposing H I spectral lines and estimating the properties of associated gas using the Autonomous Gaussian Decomposition (AGD) algorithm. We find that H I spectral lines recover physical structures in the simulation with excellen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 45 publications
4
38
1
Order By: Relevance
“…Each spectrum can be decomposed into a set of Gaussian basis functions, yielding a compressed description of the data (e.g., Haud 2000). This approach has been adopted by many previous works for studying the properties of different ISM phases (e.g., Roy et al 2013;Lindner et al 2015;Murray et al 2017;Kalberla & Haud 2018;Marchal et al 2019;Riener et al 2019), as well as detecting different classes of clouds (e.g., Haud 2008Haud , 2010. D. Lenz (2020, in preparation) created a Gaussian decomposition of this data set that is publicly available.…”
Section: Data and Gaussian Decompositionmentioning
confidence: 99%
“…Each spectrum can be decomposed into a set of Gaussian basis functions, yielding a compressed description of the data (e.g., Haud 2000). This approach has been adopted by many previous works for studying the properties of different ISM phases (e.g., Roy et al 2013;Lindner et al 2015;Murray et al 2017;Kalberla & Haud 2018;Marchal et al 2019;Riener et al 2019), as well as detecting different classes of clouds (e.g., Haud 2008Haud , 2010. D. Lenz (2020, in preparation) created a Gaussian decomposition of this data set that is publicly available.…”
Section: Data and Gaussian Decompositionmentioning
confidence: 99%
“…The τ spectra can be described as the sum of Gaussian components (e.g. Heiles & Troland 2003a;Murray et al 2017). To decompose the absorption spectra into Gaussian components we use the Autonomous Gaussian Decomposition algorithm (AGD; GaussPy) from Lindner et al (2015).…”
Section: Gaussian Decompositionmentioning
confidence: 99%
“…Because of the location of the R-C cloud, in the Galactic plane and in front of the GC, these data are especially susceptible. Murray et al (2017) investigated the recovery rate of the AGD algorithm on simulated H i spectra. They found that AGD has a very good recovery rate for simple LOS, e.g.…”
Section: Sources Of Uncertainty and Errorsmentioning
confidence: 99%
“…On smaller scales, simulations have been used to study the link between H and molecular clouds in the outer Galaxy (Douglas et al 2010), the effect of outflows on the H content of galaxies (Davé et al 2013), the observable properties and physical conditions of the Galactic interstellar H (Kim et al 2014;Murray et al 2017;Fukui et al 2018), H surface density profiles (Bahé et al 2016;Stevens et al 2019b), and the origin of spiral arms in H far beyond the optical radius of a galaxy (Khoperskov & Bertin 2016). Other studies used the H content of simulated galaxies to study gas kinematics (El-Badry et al 2018), dwarf galaxy rotation curves (Oman et al 2019), and damped Lyman-alpha absorbers (Garratt-Smithson et al 2021).…”
Section: Introductionmentioning
confidence: 99%